LXR Regulation of Brain Cholesterol: From Development to Disease. (June 2016) - Courtney, Rebecca; Landreth, Gary E.
Abstract : Liver X receptors (LXRs) are master regulators of cholesterol homeostasis and inflammation in the central nervous system (CNS). The brain, which contains a disproportionately large amount of the body's total cholesterol (∼25%), requires a complex and delicately balanced cholesterol metabolism to maintain neuronal function. Dysregulation of cholesterol metabolism has been implicated in numerous neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD). Due to their cholesterol-sensing and anti-inflammatory activities, LXRs are positioned centrally in the everyday maintenance of CNS function. This review focuses on recent research into the role of LXRs in the CNS during normal development and homeostasis and in disease states. Trends: Liver X receptors (LXRs) are master regulators of cholesterol and inflammation, are critical for brain homeostasis, and are implicated in several neurodegenerative diseases. Due to the complexity of metabolic regulation by LXRs, it has been difficult to define their roles in normal function or disease states. LXRβ is expressed ubiquitously in the CNS and performs important functions across many cell types. Emerging research into endogenous LXR ligands, which are mainly oxysterols, has determined new roles for these receptors in central nervous system (CNS) development and maintenance. Further exploration of the action of endogenous LXR ligands will better inform our understanding of its function in development and homeostasis and provide insight into the role of LXR in disease states.